2022
DOI: 10.3389/fphys.2022.990469
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the mechanism of action of dapansutrile in the treatment of gouty arthritis based on molecular docking and molecular dynamics

Abstract: Purpose: Dapansutrile is an orally active β-sulfonyl nitrile compound that selectively inhibits the NLRP3 inflammasome. Clinical studies have shown that dapansutrile is active in vivo and limits the severity of endotoxin-induced inflammation and joint arthritis. However, there is currently a lack of more in-depth research on the effect of dapansutrile on protein targets such as NLRP3 in gouty arthritis. Therefore, we used molecular docking and molecular dynamics to explore the mechanism of dapansutrile on NLRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The interactions between ligand and receptor include both covalent and non-bonded interactions, but only non-bonded interactions (van der Waals interactions, electrostatic interactions and hydrogen bonding interactions) are generally present in complex systems of drug small molecules (ligands) and proteins (receptors) ( Dasmahapatra et al., 2022 ). Therefore, AMBER 18 was used to calculate the binding free energy by MM/GBSA method in this study ( Weng et al., 2019 ; Cao et al., 2022d ).…”
Section: Methodsmentioning
confidence: 99%
“…The interactions between ligand and receptor include both covalent and non-bonded interactions, but only non-bonded interactions (van der Waals interactions, electrostatic interactions and hydrogen bonding interactions) are generally present in complex systems of drug small molecules (ligands) and proteins (receptors) ( Dasmahapatra et al., 2022 ). Therefore, AMBER 18 was used to calculate the binding free energy by MM/GBSA method in this study ( Weng et al., 2019 ; Cao et al., 2022d ).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the consistency of the binding mode can indicate the correctness of the molecular docking scheme. And the value of molecular docking score was greater than 6.5 among the target proteins and the small molecule N-0385, it was considered to be tightly bound ( Cao J. et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Gene targets screening was performed at p < 0.05 to analyze the main signaling pathways and biological processes of COVID-19. Omicshare tool platform was used to visualize the results of GO enrichment and KEGG enrichment (Cao et al, 2022b).…”
Section: Gene Target Enrichment Analysismentioning
confidence: 99%
“…On the other hand, it was revealed that CBED may exhibited a dual inhibitory effect on XOD activity and NLRP3 inflammasome activation in a dose dependent manner ( 103 ). On the basis of bioinformatics analysis and molecular docking, it was found that dapansutrile may not only selectively target NLRP3 to attenuate the inflammatory response and pyroptosis, but also block the chemotaxis and activation of inflammatory cells by regulating IL-1β, IL6, IL17A, IL18, MMP3, CXCL8, and TNF-α ( 104 ). Overall, dapansutrile, also known as OLT1177, suppressed MSU-induced joint swelling and inflammation, and may be highly effective in ameliorating GA by functioning on NLRP3 inflammasome ( 105 ).…”
Section: Therapeutic Strategies For Targeting Nlrp3 In Gamentioning
confidence: 99%